Enlightening clinical and therapeutic heterogeneity in thoracic actinomycosis: A review in bronchiectasis and non-bronchiectasis patients. (December 2021) - Cardoso, Catarina Gouveia; Freitas, Cláudia; Gomes, Isabel; Magalhães, Adriana; Fernandes, Gabriela; Guimarães, Susana; Cruz-Martins, Natália; Amorim, Adelina; Mota, Patrícia Caetano
Abstract: Actinomycosis is a rare chronic infection triggered by species of Actinomyces. Although thoracic involvement represents about 15% of human actinomycosis, its true incidence may be underestimated, not only because of its challenging diagnosis, but also because it can be treated unintentionally with antibiotics for other diseases. In this sense, this work aims at providing an up-to-date literature review on thoracic actinomycoses, with particular emphasis on presentation, diagnostic and therapeutic approaches, also paving upcoming clinical interventions from findings obtained of a presentation of a case series. Data discussed here clearly denote the rarity, non-specificity and heterogeneity of clinical presentations of the disease, reinforcing the need for individualized therapeutic approaches.